Observer Design With Better Delay Margin for Linear Time-Delay Systems - Haq, Aminul; Kucukdemiral, Ibrahim Beklan (ISTANBUL UNIV, FAC ENGINEERING, 2016)
In this paper a H-infinity type observer is proposed for linear time delay systems with delay in states. The stability of the observer is proved by Lyapunov approach. The novelty of the study is to include the state derivatives in the design. As a result, better delay margin and relaibility is obtained. Two numerical examples have been illustreted to Show the validity and effectiveness of this prescribed approach and a comparison table shows the achievement of better delay margin in comparison with corresponding Luenberger type observer.
Keywords: H-infinity observer; Lyapunov; LMI; Time-delay; STABILITY ANALYSIS; Engineering